Characterization of Genetic Variants of Uncertain Significance for the ALPL Gene in Patients With Adult Hypophosphatasia - Sanabria-de la Torre, Raquel; Martínez-Heredia, Luis; González-Salvatierra, Sheila; Andújar-Vera, Francisco; Iglesias-Baena, Iván; Villa-Suárez, Juan Miguel; Contreras-Bolívar, Victoria; Corbacho-Soto, Mario; Martínez-Navajas, Gonzalo; Real, Pedro J.; García-Fontana, Cristina; Muñoz-Torres, Manuel; et al. (Frontiers in Endocrinology, 2022)
Hypophosphatasia (HPP) a rare disease caused by mutations in the ALPL gene encoding for the tissue-nonspecific alkaline phosphatase protein (TNSALP), has been identified as a potentially under-diagnosed condition worldwide which may have higher prevalence than currently established. This is largely due to the overlapping of its symptomatology with that of other more frequent pathologies. Although HPP is usually associated with deficient bone mineralization, the high genetic variability of ALPL results in high clinical heterogeneity, which makes it difficult to establish a specific HPP symptomatology. In the present study, three variants of ALPL gene with uncertain significance and no previously described (p.DelGlu23_Lys24, p.Pro292Leu and p.His379Asn) were identified in heterozygosis in patients diagnosed with HPP. These variants were characterized at phenotypic, functional and structural levels. All genetic variants showed significantly lower in vitro ALP activity than the wild-type (WT) genotype (p-value <0.001). Structurally, p.His379Asn variant resulted in the loss of two Zn2+ binding sites in the protein dimer which may greatly affect ALP activity. In summary, we identified three novel ALPL gene mutations associated with adult HPP. The correct identification and characterization of new variants and the subsequent study of their phenotype will allow the establishment of genotype-phenotype relationships that facilitate the management of the disease as well as making it possible to individualize treatment for each specific patient. This would allow the therapeutic approach to HPP to be personalized according to the unique genetic characteristics and clinical manifestations of each patient.